Q: How do you do this problem x2 11x 10?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

X2 -11x +10=(x - 1 )(x - 10)

The equation -30 times -10 plus 11X equals -29. This is a math problem.

Not possible to be specific since you have not provided the sign of the term in x, but there are two possible factorisations; (x + 3)(x + 8) = x2 + 11x + 24 and (x - 3)(x - 8) = x2 - 11x + 24

-x2 - 11x + 26= -x2 - 13x + 2x + 26= (2x - x2) + (26 - 13x)= x(2 - x) + 13(2 - x)= (2 - x)(x + 13)

It cannot be factored because the discriminant is less than zero. Do you mean x2+11x-60 then if so it is (x-4)(x+15)

Related questions

To solve for x: x2 = 11x - 10 x2 - 11x = -10 x2 - 11x + 10 =0 (x - 1)(x - 10) = 0 x = {1, 10)

x2 = -11x - 10 x2 + 11x + 10 = 0 (x + 1)(x + 10) = 0

x2 = 11x - 10 ∴ x2 - 11x + 10 = 0 ∴ (x - 10)(x - 1) = 0 ∴ x ∈ {1, 10}

X2 -11x +10=(x - 1 )(x - 10)

21

It doesn't factor evenly if it were x**2-11x+10: x**2-11x+10 = (x-1)(x-10)

The LCM is the absolute value of x.

I assume you mean...,X2 + 11X + 10(X + 1)(X + 10)==============factored

x^3 - 121x

x2 -11x-12= (x-12)(x+1)

Can you improve the question? It's hard to tell what you mean.

If you mean x2+11x+24 then it is (x+3)(x+8) when factored